(untitled) (Conferencea, 2022)
This article is devoted to the problems of developing legal awareness and legal culture in the new Uzbek society. The article examines the current state of legal consciousness in society and suggests ways to solve this problem. There was also a discussion on the organization of activities aimed at the effective implementation of any reforms in the country. The urgency of this direction is determined by the changes that took place in the political, socio-economic, cultural and other spheres of life in the early XXI century, the emergence of new views on the nature of the state and law. There is a need to expand the legal advocacy activities carried out by all government agencies, civil society institutions and officials in the country in order to develop legal awareness and legal culture of citizens. The issues of increasing the role of the media in the implementation of legal advocacy are discussed